The molecular biology and biotechnology of flowering - Jordan, Brian R. (Wallingford, U.K. ; Cambridge, MA : CABI Publishing, 2006)
Provides an overview of the molecular mechanisms associated with flowering. This book explores three main themes: the external and internal regulation of flowering, floral development, and fertilisation and gametophyte development, and also includes chapters on the evolution of flowers, floral senescence and apomixis.
1. Photoperiodism and flowering -- 2. Vernalization -- 3. Signal transduction regulating floral development -- 4. Floral meristem identity genes -- 5. Molecular biology of floral organogenesis -- 6. Molecular developmental genetics and the evolution of flowers -- 7. Flower senescence -- 8. Developmental control and biotechnology of floral pigmentation -- 9. Biotechnology of floral development -- 10. Control of fertilization by self-incompatibility mechanisms -- 11. Stamen development : primordium to pollen -- 12. Genes regulating ovule development -- 13. The molecular biology of apomixis
Rev. ed. of: The molecular biology of flowering. c1993
Includes bibliographical references and indexes
Keywords: Plant biotechnology; Plant molecular biology; Plants, Flowering of